Bacterially sensitive nanoparticle-based dissolving microneedles of doxycycline for enhanced treatment of bacterial biofilm skin infection: A proof of concept study - Permana, Andi Dian; Mir, Maria; Utomo, Emilia; Donnelly, Ryan F. (International journal of pharmaceutics: X, 2020)
The presence of bacterial biofilms in wounds is a main issue in the healing process. Conventional therapy of bacterial biofilms is hampered by the poor penetration of antibacterial agents through the physical barrier on the infected skin and the non-specific target of antibacterial agents. Here, we present a combination approach of bacterial sensitive nanoparticles (NPs) and dissolving microneedles (MNs) of doxycycline (DOX) for improved biofilm penetration and specifically delivering DOX to the infection site. The NPs were prepared from poly(lactic-co-glycolic acid) and poly (Ɛ-caprolactone) decorated with chitosan. The release of DOX was improved with the presence of bacterial producing biofilm up to 7-fold. The incorporation of these NPs into dissolving MNs was able to significantly enhance the dermatokinetic profiles of DOX, indicated by higher retention time compared to needle-free patches. Importantly, the antibiofilm activity in ex vivo biofilm model showed that after 48 h, the bacterial bioburdens decreased up to 99.99% following the application of this approach. The results presented here assist as proof of principle for the improvement of dermatokinetic profiles and antibiofilm activities of DOX, following its formulation into bacterial sensitive NPs and delivery via MN. Future studies must explore in vivo efficacy in a suitable animal model. [Display omitted]